Sub-picosecond biphasic ultrafast all-optical switching in ultraviolet band - Dong Xiaoxiang; He Yonglin; Zhu Tao; Gao Renxian; Hu Lingyun; Li Jiayu; Ren Peiwen; Li Jian-Feng; Li Ming-De; Yang Zhilin (Nanophotonics)
Ultrafast all-optical control has been a subject of wide-spread attention as a method of manipulating optical fields using light excitation on extremely short time scales. As a fundamental form of ultrafast all-optical control, all-optical switching has achieved sub-picosecond switch speeds in the visible, infrared, and terahertz spectral regions. However, due to the lack of suitable materials, ultrafast all-optical control in the ultraviolet range remains in its early stages. We demonstrate sub-picosecond all-optical switching in the ultraviolet wavelength by designing a Si3N4-ITO Fabry–Pérot resonance aligns with the edge of the interband transition region of ITO. The response time of 500 fs achieved at a pump fluence as low as 0.17 mJ/cm2. Notably, unlike conventional binary switches (0, 1), this biphasic all-optical switch enables the modulation of optical intensity with positive, zero, and negative ΔR/R (0, 1, −1) at the same wavelength, all achieved with a switching speed of 680 fs at a pump fluence of 0.45 mJ/cm2. This work establishing a new pathway for all-optical control in the ultraviolet spectrum, the biphasic switch provides an extra degree of freedom for all-optical modulation.